Knowledge Of Ship’s Crew On Hazardous And Toxic Waste Handling Based On Application Of Government Regulation Np. 101 Year 2014 On Type 1000 Ship - yati, wartiniyati; Pangestu (Jurnal Sociohumaniora Kodepena (JSK), 2023)
Commercial ships that are engaged in shipping and have several types of ships, one of which is the type 1000 ship. The purpose of this study is the knowledge of ship crews on the handling of B3 waste on ships with an approach using government regulation number 101 of 2014.. The method used used quantitatively with direct observation and interviews. During the voyage, the ship produces hazardous and toxic waste (B3). The management of hazardous and toxic waste refers to Government Regulation No. 101 of 2014 concerning the management of hazardous and toxic waste (B3) which on board the ship during the sailing trip to the nearest port consisting of 76.9% B3 sorting/separation, 30% storage, 53.8% collection, 53.8% storage, transportation, collection and disposal 53.8%, level of understanding of regulations SOP 84.6%. Its nature is to damage the environment, endangering health, so every producer of B3 waste is due to the presence of a. activities that produce B3 waste are required to manage the B3 waste they produce. Knowledge of B3 on crew members regarding the definition of B3 is 69.2%, while B3 management is 46.2%. The results of this study found a new and different view, compared to previous research at PT. Holcim which was conducted on land, the results were as a substitute for fuel and raw materials. The results of this study used a hazardous waste management approach. Good knowledge will affect the management of b3 waste, so that it will reduce environmental pollution when the waste is in the port area. Due to the nature of the waste that is explosive like a TL lamp, it is reactive and easily ignites.